ANALISIS HUBUNGAN SISTEM INFORMASI AKADEMIK DAN KOMPETENSI TEKNIS TERHADAP EFEKTIVITAS KERJA KARYAWAN - Mochamad Wahyudi (Paradigma, 2010)
Bina Sarana Informatika (BSI) campus has an academic information system which is used as a working tool for the staffs at the Bureau for Academic Administration and Student Affair (BAAK). The use of this system requires a particular skill from each staff which is influenced by the technical competency of each user. So far, the problem which occurs concerning the system is that it has not been utilized maximally by the staffs of BAAK in their efforts on providing precise and fast services to all academicians of Bina Sarana Informatika. In this paper, the writer studies on whether there is correlation between the academic information system and technical competency of the system users towards the staffs’ working effectiveness at BAAK BSI. This research uses two independent variables and one dependent variable. The study is carried out at BAAK BSI with population and samples are the whole staffs at BAAK BSI at about 40 people. The instrument used for this study is linkert scale questionnaire, of which validity and reliability has been tested using Chi Square (c2) to see whether or not the data distribution is normal. To test the hypothesis, the writer uses simple linier regression analysis with two variables to test the first and second research hypotheses. To test the third research hypothesis, the writer uses multiple linier regression analysis. All research data is also tested using multy-colinierity and autocorrelation. The purpose of this study is to find out how great is the effect of academic information system towards staffs working effectiveness; the technical competency towards staffs working effectiveness; and academic information system and technical competency towards staffs working effectiveness. Keywords: academic information system, working effectiveness, technical competency